Extracellular Vesicle Capture by AnTibody of CHoice and Enzymatic Release (EV‐CATCHER): A customizable purification assay designed for small‐RNA biomarker identification and evaluation of circulating small‐EVs. Issue 8 (3rd June 2021) - Mitchell, Megan I.; Ben‐Dov, Iddo Z.; Liu, Christina; Ye, Kenny; Chow, Kar; Kramer, Yael; Gangadharan, Anju; Park, Steven; Fitzgerald, Sean; Ramnauth, Andrew; Perlin, David S.; Donato, Michele; et al.
Abstract: Circulating nucleic acids, encapsulated within small extracellular vesicles (EVs), provide a remote cellular snapshot of biomarkers derived from diseased tissues, however selective isolation is critical. Current laboratory‐based purification techniques rely on the physical properties of small‐EVs rather than their inherited cellular fingerprints. We established a highly‐selective purification assay, termed EV‐CATCHER, initially designed for high‐throughput analysis of low‐abundance small‐RNA cargos by next‐generation sequencing. We demonstrated its selectivity by specifically isolating and sequencing small‐RNAs from mouse small‐EVs spiked into human plasma. Western blotting, nanoparticle tracking, and transmission electron microscopy were used to validate and quantify the capture and release of intact small‐EVs. As proof‐of‐principle for sensitive detection of circulating miRNAs, we compared small‐RNA sequencing data from a subset of small‐EVs serum‐purified with EV‐CATCHER to data from whole serum, using samples from a small cohort of recently hospitalized Covid‐19 patients. We identified and validated, only in small‐EVs, hsa‐miR‐146a and hsa‐miR‐126‐3p to be significantly downregulated with disease severity. Separately, using convalescent sera from recovered Covid‐19 patients with high anti‐spike IgG titers, we confirmed the neutralizing properties, against SARS‐CoV‐2 in vitro, of a subset of small‐EVs serum‐purified by EV‐CATCHER, as initially observed with ultracentrifuged small‐EVs. Altogether our data highlight the sensitivity and versatility of EV‐CATCHER. Abstract : 'A customizable, low background, high‐affinity assay for specific immuno‐capture and release of circulating small extracellular vesicles prior to small‐RNA sequencing for identification of miRNA biomarkers or in‐vitro evaluation: The EV‐CATCHER assay (Extracellular Vesicle Capture by AnTibody of CHoice and Enzymatic Release)'.